An Operando X-ray Absorption Spectroscopy Study of a NiCu-TiO2 Photocatalyst for H-2 Evolution - Spanu, Davide; Minguzzi, Alessandro; Recchia, Sandro; Shahvaranfard, Fahimeh; Tomanec, Ondrej; Zboril, Radek; Schmuki, Patrik; Ghigna, Paolo; Altomare, Marco (ACS Catalysis, 2020)
Cu- or Ni-decorated semiconductors represent a potential low-cost alternative to noble-metal-modified photocatalysts. Even more effective are bimetallic NiCu nanoparticles, which can provide a remarkable photocatalytic H-2 evolution enhancement compared to single-element Cu or Ni systems. The main concern of such alloyed co-catalysts is their activity with respect to alteration of their elemental composition and oxidation state over reaction time. Ex situ characterization techniques provide controversial interpretations of the co-catalytic role of the individual elements. Hypotheses such as the in situ reduction of "native" Ni or Cu species during photocatalysis, the oxidation of metallic Cu or Ni into oxides or hydroxides, or the formation of p-n junctions or core/shell structures have been proposed. Herein, we present an operando X-ray absorption spectroscopy study of a NiCu-TiO2 system under UV light illumination in ethanol-water solutions, i.e., under photocatalytic H-2 evolution conditions. The experimental approach allows for monitoring in real time chemical changes that take place in the co-catalyst under intermittent illumination, i.e., under light on-off cycles. We show that while Ni and Cu are partially oxidized in the as-formed NiCu co-catalyst (air-formed surface oxides or hydroxides) and undergo partial dissolution in the liquid phase under dark conditions, such Ni and Cu oxidized and dissolved species are reduced/redeposited as a bimetallic NiCu phase at the TiO2 surface under illumination. The dissolution/redeposition mechanism is triggered by TiO2 conduction band electrons. We not only prove a UV-light-induced healing of the NiCu co-catalyst but also unambiguously demonstrate that the species responsible for the strongly enhanced photocatalytic H-2 evolution of NiCu nanoparticles are the metallic states of Ni and Cu.
CRIS-Team WoS Importer:2020-09-11

Comparison of the sputtered TiO2 anatase and rutile thin films as electron transporting layers in perovskite solar cells - Shahvaranfard, Fahimeh; Li, Ning; Hosseinpour, Saman; Hejazi, Seyedsina; Zhang, Kaicheng; Altomare, Marco; Schmuki, Patrik; Brabec, Christoph (Nano Select, 2021)
We examine comparatively the performance of sputtered TiO2 rutile and anatase thin films as an electron transport layer (ETL) inMAPbI3-based perovskite solar cells. Both anatase and rutile TiO2 ETLs are deposited (on fluorine-doped tin oxide [FTO] substrates) by magnetron sputtering in the form of nanocrystalline thin films. We systematically investigate the role of crystallographic phase composition of TiO2 ETLs on the photovoltaic performance of perovskite solar cells. The champion power conversion efficiencies (PCEs) of 18.4% and 17.7% under reverse scan mode are obtained for perovskite solar cells based on TiO2 anatase and TiO2 rutile ETL, respectively. The results show that the magnetron sputtering deposited ETLs differ from each other only in their phase composition while the overall performance of the devices is not greatly affected by the crystallographic phase of the TiO2 ETLs. Our results point to an important fact that for a proper and reliable comparison between the performance of TiO2 anatase and rutile ETLs, it is crucial to investigate films of similar morphology and structure that are synthesize under similar condition
Keywords: magnetron sputtering; perovskite solar cell; TiO2 anatase; TiO2 rutile

Dewetting of PtCu Nanoalloys on TiO2 Nanocavities Provides a Synergistic Photocatalytic Enhancement for Efficient H2 Evolution - Shahvaranfard, Fahimeh; Ghigna, Paolo; Minguzzi, Alessandro; Wierzbicka, Ewa; Schmuki, Patrik; Altomare, Marco (ACS Applied Materials and Interfaces, 2020)
We investigate the co-catalytic activity of PtCu alloy nanoparticles for photocatalytic H2 evolution from methanol-water solutions. To produce the photocatalysts, a few-nanometer-thick Pt-Cu bilayers are deposited on anodic TiO2 nanocavity arrays and converted by solid-state dewetting via a suitable thermal treatment into bimetallic PtCu nanoparticles. X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS) results prove the formation of PtCu nanoalloys that carry a shell of surface oxides. X-ray absorption near-edge structure (XANES) data support Pt and Cu alloying and indicate the presence of lattice disorder in the PtCu nanoparticles. The PtCu co-catalyst on TiO2 shows a synergistic activity enhancement and a significantly higher activity toward photocatalytic H2 evolution than Pt- or Cu-TiO2. We propose the enhanced activity to be due to Pt-Cu electronic interactions, where Cu increases the electron density on Pt, favoring a more efficient electron transfer for H2 evolution. In addition, Cu can further promote the photoactivity by providing additional surface catalytic sites for hydrogen recombination. Remarkably, when increasing the methanol concentration up to 50 vol % in the reaction phase, we observe for PtCu-TiO2 a steeper activity increase compared to Pt-TiO2. A further increase in methanol concentration (up to 80 vol %) causes for Pt-TiO2 a clear activity decay, while PtCu-TiO2 still maintains a high level of activity. This suggests improved robustness of PtCu nanoalloys against poisoning from methanol oxidation products such as CO.
CRIS-Team Scopus Importer:2020-09-11
Keywords: copper; H2 evolution; photocatalysis; platinum; PtCu alloy nanoparticle; solid-state dewetting; TiO2 nanotube

Engineering of the Electron Transport Layer/Perovskite Interface in Solar Cells Designed on TiO2 Rutile Nanorods - Shahvaranfard, Fahimeh; Altomare, Marco; Hou, Yi; Hejazi, Seyedsina; Meng, Wei; Osuagwu, Emeka Benedict; Li, Ning; Brabec, Christoph; Schmuki, Patrik (Advanced Functional Materials, 2020)
The engineering of the electron transport layer (ETL)/light absorber interface is explored in perovskite solar cells. Single-crystalline TiO2 nanorod (NR) arrays are used as ETL and methylammonium lead iodide (MAPI) as light absorber. A dual ETL surface modification is investigated, namely by a TiCl4 treatment combined with a subsequent PC61BM monolayer deposition, and the effects on the device photovoltaic performance were evaluated with respect to single modifications. Under optimized conditions, for the combined treatment synergistic effects are observed that lead to remarkable enhancements in cell efficiency, from 14.2% to 19.5%, and to suppression of hysteresis. The devices show J(SC), V-OC, and fill factor as high as 23.2 mA cm(-2), 1.1 V, and 77%, respectively. These results are ascribed to a more efficient charge transfer across the ETL/perovskite interface, which originates from the passivation of defects and trap states at the ETL surface. To the best of our knowledge, this is the highest cell performance ever reported for TiO2 NR-based solar cells fabricated with conventional MAPI light absorber. Perspective wise, this ETL surface functionalization approach combined with more recently developed and better performing light absorbers, such as mixed cation/anion hybrid perovskite materials, is expected to provide further performance enhancements.
Keywords: defect passivation; PC61BM; perovskite solar cells; TiCl4; TiO2 nanorods